Librarians as community partners : an outreach handbook - Smallwood, Carol, 1939- (American Library Association, 2010)
Includes 66 focused snapshots of outreach in action, this resource reflects the creative solutions of librarians searching for new and innovative ways to build programs that meet customer needs while expanding the library's scope into the community.